ดีวัลคาไนเซชันของยางธรรมชาติวัลคาไนซ์โดยแบคทีเรียที่คัดแยกได้จากดินที่ปนเปื้อนซัลเฟอร์ในประเทศไทย - เบญจา แก้วเพ็ชร (จุฬาลงกรณ์มหาวิทยาลัย, 2018)
Biological devulcanization is one of alternative methods to solve the problem of rubber waste. The advantage of this process is environmentally friendly and low cost. Thus, this research aims to isolate the desulfurized bacteria from sulfur-contaminated soil areas in Thailand for biological devulcanization, leading to obtain reclaim rubber or devulcanized rubber for recycle process. Bacillus cereus showed the efficiency to desulfurize dibenzothiophene at 88.1±0.1%. Then, B. cereus was devulcanized natural rubber vulcanizates (NRV) with different curing systems; (conventional vulcanization: CV), (semi-efficient vulcanization: Semi-EV) and (efficient vulcanization: EV)). It was found that NRV with the CV system showed the highest of sulfur removal (27.1±0.4) at under pH 7 at room temperature (30±2oC) for 30 days of devulcanization time. The crosslink density of devulcanized rubber was decreased to 70.2%, resulting in the decreased gel fraction. Moreover, the effect of particle size, pH and temperature were studied in order to optimize the devulcanized condition. The results showed that the sulfur removal in small particle (Ø=0.3-0.4 mm) of devulcanized rubber was higher than that in the large particle (Ø=2.0-2.7 mm) of devulcanized rubber. The optimized condition of B. cereus for devulcanization was under pH 5 at room temperature (30±2oC) for 20 days. Under this condition, the percentage of sulfur removal of the devulcanized rubber was 64.3±0.1%. The ground tire rubber (GTR) was also devulcanized by B. cereus. As a result, the sulfur content of devulcanized GTR was decreased (40.2±0.2%). Finally, the different devulcanized rubber ratios (5-20 parts by weight per hundred parts of rubber: phr) were mixed with virgin rubber. It was found that by increasing devulcanized rubber, the tensile strength and elongation at break of revulcanized rubber were decreased, while the hardness was increased. Therefore, the devulcanized rubber obtained from devulcanization by B. cereus could be used as raw material on vulcanization process.